UHC in Morocco: a bottom-up estimation of public hospitals' financing size based on a costing database - El Houcine Akhnif; Abdelouahab Belmadani; Awad Mataria; Maryam Bigdeli (Health Economics Review, 2024)
Abstract Background Morocco is engaged in a health system reform aimed at generalizing health insurance across the whole population by 2025. This study aims to build a national database of costs at all levels of public hospitals in Morocco and craft this database as a resource for further use in a strategic purchasing system. It also aims at estimating the funding gap and the budget that should be secured for public hospitals in Morocco to fully play their roles in the current ambitious reform. Method A costing study was implemented in 39 hospitals in 12 regions of Morocco (10 provincial hospitals, 11 regional hospitals, and 18 teaching hospitals). Using the hospital costing approach, we adapted and validated nationally our methodology to generate a database of unit costs based on data from 2019. All perspectives on cost were considered. Data collection was performed by cadres from MoH and facilitated by the WHO country office in Morocco. The production of the cost database allowed the development of a bottom-up estimation of the financing size for public health hospitals. Results The study showed the feasibility of large-scale costing in the context of Morocco. The ownership of MoH and adherence to the process ensured the high quality of the collected data. There are many differences in unit costs for the same services moving from one hospital to another, which indicates existing inefficiencies. The database will contribute to shaping the strategic purchasing mechanism within the generalized health insurance schemes. The studied hospitals could be used as references to systematically update the billing system for health insurance.